Analysis of influencing factors on recurrence and metastasis of pT1b ~ pT4aNOM0 esophageal squamous cell carcinoma after radical surgery in Northeast Sichuan region - Wenxia Ren; Lei Yu; Yu Cui; Daiyuan Ma (BMC Surgery)
Abstract Background The incidence and mortality rates of esophageal cancer are high, yet public awareness of this disease remains low, particularly in the northeastern Sichuan region. This study aims to investigate the factors influencing recurrence and metastasis after radical surgery for pT1b ~ pT4aN0M0 esophageal squamous cell carcinoma in northeastern Sichuan, providing a personalized reference for postoperative follow-up of patients undergoing radical esophagectomy for esophageal squamous cell carcinoma. Methods A retrospective analysis was conducted on the clinical data of 151 patients with pT1b to pT4aN0M0 esophageal squamous cell carcinoma who underwent radical surgery in the northeastern Sichuan region. Based on postoperative tumor recurrence, the patients were divided into a recurrence group (76 cases) and a non-recurrence group (75 cases). The clinical data of the two groups were compared to analyze the factors influencing postoperative tumor recurrence in patients with pT1b to pT4aN0M0 esophageal squamous cell carcinoma. Results Univariate analysis of recurrence after radical surgery for esophageal squamous cell carcinoma (ESCC) in the northeastern Sichuan region at stages pT1b to pT4aNOM0 revealed that T stage, differentiation degree, gross tumor type, smoking history, and drinking history were factors influencing postoperative recurrence (all P < 0.05). Logistic regression analysis showed that T stage, gross tumor type, and smoking history were independent factors influencing postoperative recurrence. Univariate analysis of recurrence patterns revealed that the T stage and TNM stage were significant factors influencing recurrence and metastasis patterns after radical surgery for ESCC (all P < 0.05). Logistic regression analysis revealed that the T stage was an independent factor influencing the risk of distant metastasis after radical surgery for ESCC. The 1-year, 2-year, and 3-year disease-free survival rates for the 76 patients with recurrence were 68.4%, 40.8%, and 19.7%, respectively, with a median disease-free survival of 18 months (range: 3–57 months). There were 50 cases (65.8%) of isolated local recurrence, 11 cases (14.5%) of isolated distant metastasis, and 15 cases (19.7%) of local recurrence combined with distant metastasis. Univariate analysis revealed that T stage, TNM stage, histological grade, and gross tumor type were factors influencing post-operative disease-free survival (all P < 0.05). Multivariate analysis identified T stage and gross tumor type as independent factors affecting disease-free survival after radical surgery. Conclusions For postoperative patients with pT1b ~ pT4aNOM0 esophageal squamous cell carcinoma in the northeastern Sichuan region, those with advanced T stages and a history of smoking may be more prone to recurrence, and patients with constricted, ulcerated, and mushroom-umbrella types may be more likely to relapse than those with medullary type. For postoperative patients in this region, the later the T stage, the shorter the disease-free survival and the higher the likelihood of distant metastasis. Therefore, individualized postoperative adjuvant therapy should be considered.